The Influence of Purchasing Organic Food Among Expatriates in Indonesia - Genoveva Genoveva; Akram Alamodi (Indonesian Journal of Business and Entrepreneurship (IJBE), 2022)
The purpose of this study was to explore the factors that influence purchasing decisions expart to organic food. Environmental issues make a number ofmany people pay special attention to environmental sustainability. In Indonesia, a healthy lifestyle by consuming organic products has become a trend among the upper- middle class of some Indonesians, but most of the consumers of organic food in Indonesia are expatriates. The variables that influence the decision to purchase organic food that will be used in this research are Customer Attitude, Personal Norms, Social Norms, Impending Barriers and Marketing Strategies on Purchase Decisions. This study is a quantitative research using online questionnaires in data collection. Respondents are expatriates in greater Jakarta, as many as 165 people. The data is processed by SPSS. The findings of this study are consumer attitudes, personal norms, and marketing strategies have a significant influence on purchasing decisions, while social norms and future barriers do not. The variable that most influences the decision to purchase organic food is the marketing strategies which contributes 33.6%. Keywords: customer attitude, impending barriers, marketing strategies, personal norm, social norms